METHODOLOGY OF TEACHING ENGLISH (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Today, the main attention is focused on the student, his personality and unique inner world. Therefore, the main goal of a modern teacher is to choose methods and forms of organization of educational activities students that optimally correspond to the set goal of personal development. In recent years, the issue of using new information technologies in schools has been raised more and more. It is not only new technical means, but also new forms and methods of teaching, a new approach to the educational process. The main goal of teaching foreign languages is to form and develop the communicative culture of schoolchildren, to teach them to practice a foreign language.